Suture Knot Externalization Modification of the Fasanella‐Servat Technique for Involutional Ptosis. (10th December 2020) - Ghodke, Ameer; Mims, Mark M.; Shockley, William W.; Clark, J. Madison
Abstract : View Video S1 Laryngoscope, 131:1492–1496, 2021